Biofortified Maize Improves Selenium Status of Women and Children in a Rural Community in Malawi: Results of the Addressing Hidden Hunger With Agronomy Randomized Controlled Trial - Joy, Edward J. M.; Kalimbira, Alexander A.; Sturgess, Joanna; Banda, Leonard; Chiutsi-Phiri, Gabriella; Manase, Hastings; Gondwe, Jellita; Ferguson, Elaine L.; Kalumikiza, Zione; Bailey, Elizabeth H.; Young, Scott D.; Matandika, Limbanazo; et al. (Frontiers in Nutrition, 2022)
Background Selenium deficiency is widespread in the Malawi population. The selenium concentration in maize, the staple food crop of Malawi, can be increased by applying selenium-enriched fertilizers. It is unknown whether this strategy, called agronomic biofortification, is effective at alleviating selenium deficiency. Objectives The aim of the Addressing Hidden Hunger with Agronomy (AHHA) trial was to determine whether consumption of maize flour, agronomically-biofortified with selenium, affected the serum selenium concentrations of women and children in a rural community setting. Design An individually-randomised, double-blind placebo-controlled trial was conducted in rural Malawi. Participants were randomly allocated in a 1:1 ratio to receive either intervention maize flour biofortified with selenium through application of selenium fertilizer, or control maize flour not biofortified with selenium. Participant households received enough flour to meet the typical consumption of all household members (330 g capita–1 day–1) for a period of eight weeks. Baseline and endline serum selenium concentration (the primary outcome) was measured by inductively coupled plasma mass spectrometry (ICP-MS). Results One woman of reproductive age (WRA) and one school-aged child (SAC) from each of 180 households were recruited and households were randomised to each group. The baseline demographic and socioeconomic status of participants were well-balanced between arms. No serious adverse events were reported. In the intervention arm, mean (standard deviation) serum selenium concentration increased over the intervention period from 57.6 (17.0) µg L–1 (n=88) to 107.9 (16.4) µg L–1 (n=88) among WRA and from 46.4 (14.8) µg L–1 (n=86) to 97.1 (16.0) µg L–1 (n=88) among SAC. There was no evidence of change in serum selenium concentration in the control groups. Conclusion Consumption of maize flour biofortified through application of selenium-enriched fertilizer increased selenium status in this community providing strong proof of principle that agronomic biofortification could be an effective approach to address selenium deficiency in Malawi and similar settings.